Differential dysfunctions related to alcohol and cannabis use disorder symptoms in reward and error-processing neuro-circuitries in adolescents. (April 2019) - Aloi, Joseph; Meffert, Harma; White, Stuart F.; Blair, Karina S.; Hwang, Soonjo; Tyler, Patrick M.; Thornton, Laura C.; Crum, Kathleen I.; Adams, Kathryn O.; Killanin, Abraham D.; Filbey, Francesca; Pope, Kayla; et al.
Abstract: Alcohol and cannabis are two of the most commonly used substances by adolescents and are associated with adverse medical and psychiatric outcomes. These adverse psychiatric outcomes may reflect the negative impact of alcohol and/or cannabis abuse on neural systems mediating reward and/or error detection. However, work indicative of this has mostly been conducted in adults with Alcohol and/or Cannabis Use Disorder (i.e., AUD and CUD), with relatively little work in adolescent patients. Furthermore, of the work that has been conducted in adolescents, groups were based on categorical diagnoses of AUD and/or CUD, so the relationship between AUD and/or CUD symptom severity in adolescents and neural dysfunction is unclear. We used a Monetary Incentive Delay (MID) task to examine the relationship between AUDIT and/or CUDIT scores and functional integrity of neuro-circuitries mediating reward processing and error detection within 150 adolescents. Our findings indicate that AUDIT score is negatively related to activity in reward processing neuro-circuitry in adolescents. However, CUDIT score is negatively related to activity in brain regions involved in error detection. Each of these relationships reflected a medium effect size (Partial-η 2 0.09-0.14). These data suggest differential impacts of AUD and CUD on reward versus error detection neuro-circuitries within the adolescent brain.